RUSSIAN CULTURAL (CIVILIZATIONAL) CODE: IDENTITY AND POLICY - O. Yakhshiyan (Вестник университета)
The concept of a single cultural (civilizational) code as a meaningful characteristic of the cultural component of the Russian national (political) identity has been considered. The concept of a civilizational code presupposes an understanding of Russia both as a modern nation-state and as a historical civilization- state. It follows, that Russian identity can be characterized as being national-civilizational. The Russian cultural (civilizational) code is shown as a decisive condition for the unity and stability of Russian statehood and Russian civilization. The impact of the Russian cultural (civilizational) code on the ethnic identity of non-Russian citizens of our country is not assimilation, but acculturation. Russian civilizational identity dialectically integrates ethno-cultural and confessional identities of Russians, while responding to the request of the Russian ethnic identity. Reproduction of the Russian cultural (civilizational) code is implemented by means of linguistic, cultural, symbolic, historical policies, policies in the field of adaptation and integration of migrants, etc.